Adverse childhood experiences and health outcomes: a 20-year real-world study - Martins, Bárbara; Taveira-Gomes, Tiago; Gomes, Joana Costa; Vidal-Alves, Maria João; Magalhães, Teresa (Frontiers in Medicine, 2025)
Introduction Adverse childhood experiences (ACEs) refer to traumatic life events occurred in childhood that comprise abuse (e.g., psychological, physical, sexual), neglect (psychological and physical), indirect violence or household dysfunctions. Such experiences ultimately lead to severe short-, medium- and long-term consequences for the victim’s health. The goal of this study is to analyze the prevalence of health outcomes in children <16 years of age, who were suspected of ACEs by physicians. The specific objectives consist of analyzing 3 health outcome groups: (a) traumatic injuries and intoxications; (b) mental health disorders; and (c) physical disorders. Methods We performed a real-world, retrospective, observational, cross-sectional, and multicentric study, using complementary data from electronic health records and healthcare registries from the local healthcare unit of Matosinhos, generated between January 1, 2001, and December 31, 2021 (total child population <16 years observed during that period=40 536). Keywords and ICD-9, ICD-10, and ICPC-2 codes were applied to find data on the victims. Results Just over 2% of children were referred to as victims in the available information (n=918). Social problems, injuries and intoxications, mental health disorders, and physical disorders were observed at higher percentages in suspected victims than in the total analyzed population. Discussion These results reveal that child victims of ACEs may be underdiagnosed, which, given the aforementioned (and described in the literature) severe consequences for their current and future health, should be taken as a critical warning for healthcare professionals. Detections and reports are fundamental for early treatment, aiming to avoid an escalation of damage and prevent re-victimization.